Private cloud infrastructure for Dyslexia Association of Malaysia / Mohamad Sabri Zamhuri - Zamhuri, Mohamad Sabri (2014)
Cloud computing is a concept that has become increasingly popular in recent years through an increase in Internet connection capabilities, virtualization possibilities, and commercial successes. It offers functionalities over the telecommunications network in the form of services instead of as a delivered product. This in combination with that the user is agnostic to the underlying technology provides advantages like increased flexibility in the technical solution and payment model, robustness and availability, as well as security in size. The downside of cloud computing is for example the Internet connection dependency, loss of control over the data, and the risk of vendor lock-in. These advantages and disadvantages make the decision between an on premise resource and a cloud computing service complex. This case-based action research aims to provide researchers and IT personnel, like administrators, architects and designers, tools and guidelines to reduce the decision complexity. It is done by a presentation of an architectural solution that has the potential to boost the benefits of cloud computing, construction of an evaluation scorecard that indicates if a system is suitable for cloud computing or not and by identifying possible cloud computing alternatives to the systems indicated by the scorecard.